2017
DOI: 10.3390/rs9070691
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Seasonal Patterns of Photosynthesis, Fluorescence, and Reflectance Indices in Boreal Trees

Abstract: Tree species in the boreal forest cycle between periods of active growth and dormancy alter their photosynthetic processes in response to changing environmental conditions. For deciduous species, these changes are readily visible, while evergreen species have subtler foliar changes during seasonal transitions. In this study, we used remotely sensed optical indices to observe seasonal changes in photosynthetic activity, or photosynthetic phenology, of six boreal tree species. We evaluated the normalized differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 55 publications
8
52
0
Order By: Relevance
“…3S, supplement available online), and PRI and ETR were both correlated with F v /F m (although not with each other) across species means (Fig. 4B), consistent with prior research , Peguero-Pina et al 2008, Springer et al 2017.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…3S, supplement available online), and PRI and ETR were both correlated with F v /F m (although not with each other) across species means (Fig. 4B), consistent with prior research , Peguero-Pina et al 2008, Springer et al 2017.…”
Section: Discussionsupporting
confidence: 87%
“…Habitats and regions vary in the functional composition and evolutionary history of their constituent species, and understanding the comparative physiology -including photoprotective physiology -of these species can help explain ecosystem-level properties. Previous studies have revealed large variation in photoprotective strategies among tree species in a single stand (Gamon et al 2005), and between functionally distinct species that often inhabit different niches, such as deciduous and evergreen plants , Springer et al 2017. Given these findings, characterizing the extent of variation in photoprotective strategies among species from a single site could help in understanding how a range of strategies can succeed in a uniform environment.…”
Section: Introductionmentioning
confidence: 99%
“…() show green‐up and budburst to occur 1–2 weeks prior to SIF‐based GPP onset in northern high latitude deciduous tundra ecosystems. Moreover, leaf‐level SIF measurements show close correspondence to photochemical reflectance index and chlorophyll carotenoid index optical indices during spring photosynthetic activation (from gas exchange measurements) in boreal evergreens, reflecting a reversal of nonphotochemical quenching and leaf pigments in spring with changes in chloroplast functioning during cold dehardening (Springer, Wang, & Gamon, ; Wong & Gamon, ). Especially in evergreens, SIF remote sensing has potential to provide a powerful measure of the reactivation of photosynthesis in spring at large spatial scales, which is otherwise invisible and difficult to assess with reflectance‐based optical indices (Walther et al., ; Wong & Gamon, ).…”
Section: Introductionmentioning
confidence: 84%
“…Increasing pigmentation in fall functions to shed more absorbed energy as NPQ than SIF over winter months (Demmig‐Adams & Adams, ; MĂŒller, Li, & Niyogi, ; Ottander et al., ; Porcar‐Castell, ) and in early spring with increasing exposure to harmful radiation (Arneth et al., ). Increases in absorbed light and temperature in spring during the cold dehardening period cause relative declines in carotenoid pigments and increases in chlorophyll concentrations, leading to increasing photosynthetic activity, reduced NPQ, and increased dissipation of absorbed light as SIF (Springer et al., ; Wong & Gamon, ). The increase in SIF and GPP in evergreens is gradual due to the gradually changing pigment ratios of carotenoids and chlorophyll (Wong & Gamon, ).…”
Section: Discussionmentioning
confidence: 99%
“…Water stress conditions would reduce chlorophyll levels in plant leaves ultimately effecting photosynthesis and leaf development (Sanchez et al, 1983). Decrease in chlorophyll fluorescence will reduce NDVI and LAI values (Springer et al, 2017). Wheat, rice, cotton and sugarcane are cash crops for study area, which not only fulfill food and fabric needs but also a major source of economic benefit to grower.…”
Section: Crop Rotation Phenologymentioning
confidence: 99%